Methods for measuring financial toxicity after cancer diagnosis and treatment: a systematic review and its implications - Witte, Julian; Mehlis, Katja; Winkler, Eva C. (Annals of oncology, 2019)
Patients experiencing financial distress as a side-effect of cancer are not only reported in the United States, but also in third-party payer healthcare systems in Europe. Since validated survey instruments are a prerequisite for robust and comparable results, we aimed to compile and classify available instruments to enable both a better understanding of the underlying construct of financial toxicity and to facilitate further studies that are adjustable to various healthcare systems. We did a systematic literature search on studies that provide data on perceived cancer-related financial distress experienced by adult patients using PubMed, CINAHL and Web of Science databases up to 2018. We analyzed all detected instruments, items domains and questions with regard to their wording, scales and the domains of financial distress covered. Among 3298 records screened, 41 publications based on 40 studies matched our inclusion criteria. Based on the analysis of 352 different questions we identified 6 relevant subdomains that represent perceptions of and reactions to experienced financial distress: (i) active financial spending, (ii) use of passive financial resources, (iii) psychosocial responses, (iv) support seeking, (v) coping with care or (vi) coping with ones’ lifestyle. We found an inconsistent coverage and use of these domains that makes it difficult to compare and quantify the prevalence of financial distress. Moreover, some existing instruments do not reflect relevant domains for patients in third-party payer systems. There is neither a consistent understanding of the construct of financial burden nor do available instruments cover all relevant aspects of a patients’ distress perception. We encourage using the identified six domains to further develop survey instruments and adjust them to different health systems.
Gesehen am 21.10.2019